2018
DOI: 10.1097/md.0000000000010948
|View full text |Cite
|
Sign up to set email alerts
|

Impact of atrial arrhythmias after esophagectomy on recovery

Abstract: Background:Postoperative atrial arrhythmias (PAAs) are common complications after esophagectomy, however research findings are contradicted on the prognosis. Therefore this meta-analysis was conducted to determine whether PAAs after esophagectomy had an impact on prognosis.Methods:Studies comparing prognosis between patients with and without PAAs after esophagectomy were searched in EMBASE, MEDLINE, and the Cochrane Register. Primary prognosis was perioperative mortality, and secondary prognoses were postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…3,11,12 In these studies, complications of infections (anastomotic leakage and sepsis) were consistently associated with new-onset atrial fibrillation. 3,12 However, a few studies have been conducted to assess the effects of MIE, which plays a major role in reducing infectious complications 13,14 with no significant impact on anastomotic leakage. [15][16][17] In the present study, we assessed the link between MIE and the incidence of atrial fibrillation after esophagectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,11,12 In these studies, complications of infections (anastomotic leakage and sepsis) were consistently associated with new-onset atrial fibrillation. 3,12 However, a few studies have been conducted to assess the effects of MIE, which plays a major role in reducing infectious complications 13,14 with no significant impact on anastomotic leakage. [15][16][17] In the present study, we assessed the link between MIE and the incidence of atrial fibrillation after esophagectomy.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis found that patients with POAF had higher perioperative mortality, longer hospital stays, and a greater incidence of complications. 3 Risk factors, demographic data 4 and medical history 5 were all shown to play a role in the development of POAF.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, landiolol did not reduce the frequency of Clavien-Dindo complications in patients undergoing esophagectomy. In this patient population, AF may occur as a prodromal symptom of complications because these two entities are closely related [18][19][20]. An earlier randomized trial showed that landiolol reduced the proportion of Clavien-Dindo complications, although the protocol was switched to an open-label design after AF was diagnosed [11].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative atrial fibrillation (POAF) is one of the most common complications of esophagectomy that often occur within 3 days after esophagectomy [1]. Studies showed that POAF could lead to a longer hospital stay and a greater incidence of other complications [2]. POAF risk is higher among patients who are older [3], racial/ethnic minorities [4], taking perioperative medications such as β-blocker [5], and having hypertension [6] or operative trauma [7].…”
Section: Introductionmentioning
confidence: 99%